The distribution of mycorrhizal fungi on tree bark correlates with the host preference of the tropical epiphytic orchid Bulbophyllum variegatum on La Réunion island - Rémi Petrolli; Rosa Kemmerling; Géromine Collobert; Eve Hellequin; Tony Robinet; Neil Lancaster; David L. Roberts; Thierry Pailler; Claudine Ah-Peng; Marc-André Selosse; Florent Martos (Fungal Ecology, 2026)

Laser Induced Breakdown Spectroscopy (LIBS) for whole rock geochemistry - Fernando F. Fontana; Ben van der Hoek; Steven Tassios; Caroline Tiddy; Jessica Stromberg; Neil Francis; Yulia A. Uvarova; David G. Lancaster (Journal of Geochemical Exploration, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Scope for genetic rescue of an endangered subspecies though re‐establishing natural gene flow with another subspecies - Katherine A. Harrisson; Alexandra Pavlova; Anders Gonçalves da Silva; Rebecca Rose; James K. Bull; Melanie L. Lancaster; Neil Murray; Bruce Quin; Peter Menkhorst; Michael J. L. Magrath; Paul Sunnucks (Molecular Ecology, 2016)
Genetic diversity is positively linked to the viability and evolutionary potential of species but is often compromised in threatened taxa. Genetic rescue by gene flow from a more diverse or differentiated source population of the same species can be an effective strategy for alleviating inbreeding depression and boosting evolutionary potential. The helmeted honeyeater Lichenostomus melanops cassidix is a critically endangered subspecies of the common yellow‐tufted honeyeater. Cassidix has declined to a single wild population of ~130 birds, despite being subject to intensive population management over recent decades. We assessed changes in microsatellite diversity in cassidix over the last four decades and used population viability analysis to explore whether genetic rescue through hybridization with the neighbouring Lichenostomus melanops gippslandicus subspecies constitutes a viable conservation strategy. The contemporary cassidix population is characterized by low genetic diversity and effective population size ( N e gippslandicus to cassidix has declined substantially relative to pre‐1990 levels and argue that natural levels of gene flow between the two subspecies should be restored. Allowing gene flow (~4 migrants per generation) from gippslandicus into cassidix (i.e. genetic rescue), in combination with continued annual release of captive‐bred cassidix (i.e. demographic rescue) , should lead to positive demographic and genetic outcomes. Although we consider the risk of outbreeding depression to be low, we recommend that genetic rescue be managed within the context of the captive breeding programme, with monitoring of outcomes.